Generating Orthophotos from Curved Heritage Interiors Using Open-Source Photogrammetry: A Case Study of Saint Theodore Church, Cappadocia - Ipek, Tacettin Yucel; Kulavuz, Bahadir; Ozata, Serife; Bakirman, Tolga; Bayram, Bulent (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Curved domes, vaults, and apses in heritage architecture often contain frescoes and inscriptions of immense cultural value, yet their documentation remains challenging. Conventional orthophotos assume planarity, producing distortions that limit iconographic interpretation and conservation mapping. While commercial software offers partial solutions, high costs and limited transparency hinder adoption by many institutions. This study introduces a fully open-source workflow for producing metrically accurate orthophotos of curved interiors, demonstrated on the richly painted rock-hewn St Theodore Church in Cappadocia. The pipeline integrates photogrammetric reconstruction in Meshroom with 3D point-cloud segmentation, primitive fitting, and surface unrolling in CloudCompare, followed by Poisson meshing and orthographic rendering. Validation against CAD measurements confirmed geometric fidelity, with median errors of similar to 1-2%. The resulting CAD-ready orthophotos enable detailed tracing of mural registers, epigraphic analysis, and quantitative conservation studies. By providing a low-cost, reproducible, and accessible alternative to proprietary tools, the proposed method empowers heritage professionals to create distortion-controlled documentation of complex interiors and supports long-term monitoring and preservation efforts.
Keywords: Orthophoto; surface unrolling; photogrammetry; curved interiors; cultural heritage; Archaeology; Art; Chemistry; Spectroscopy